Detection and endodontic management of radix entomolaris: Report of case series - A. R. Vivekananda Pai; Rachit Jain; Ashwini S. Colaco (Wolters Kluwer Medknow Publications, 2014)
Radix entomolaris (RE) is considered to be an Asiatic trait. However, its prevalence in Indian population is found to be lower than in other Asian races. Nevertheless, its awareness and identification is vital to achieve endodontic success. This article presents a review on clinical approach and a case series on the detection and endodontic management of RE in mandibular first molars. Radix entomolaris was detected by identifying the presence of a double or extra root outline in the preoperative radiograph, modifying the access opening and closely inspecting the pulp chamber and was endodontically treated following cleaning, shaping, and obturation of the canals. Achieving the endodontic success in the presence of an RE requires knowledge about its prevalence, diagnosis, morphology, canal configuration, and clinical approach.